Mengembangkan Kreativitas Pembuatan Buket Bunga Di Kalangan Jiwa Muda Berwirausaha - Firda Septiana Sanar; Rais Rais; Hemenius R Solossa; Ria Angela; Susana Magdalena Welly Muskita (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research examines the importance of cultivating an entrepreneurial spirit and character in the younger generation, as well as the potential and opportunities for the flower bouquet business as an example of young people's creativity in facing the modern era. Through literature reviews and practical observations, this research explores the vital role of entrepreneurship in economic and social development, as well as its benefits for individuals and society. The main focus is given to the flower bouquet business as a case study, explaining the manufacturing process, tools and materials used, and the market potential it has. The research results show that the development of an entrepreneurial spirit in the younger generation not only contributes to economic growth, but also facilitates self-actualization and social innovation. The flower bouquet business was identified as a promising opportunity with affordable initial capital and significant profit potential. This research concludes that encouraging entrepreneurship among the younger generation, such as through the flower bouquet business, can be an effective strategy for increasing creativity, financial independence and positive contributions to society.